2012
DOI: 10.1016/j.ejvs.2012.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the Delay to Carotid Endarterectomy in Symptomatic Patients with Carotid Stenosis – Outcome of an Intervention

Abstract: This study demonstrates how it is possible to shorten the delay to carotid endarterectomy among patients with symptomatic carotid stenosis with quite simple changes made in the surgical and the neurological unit. However, affecting only the in-hospital delay, optimal results are still not achieved, as our study corroborates. At the same time, our study points out the areas where we could and should still focus more carefully in order to minimise the delay and maximise the expected benefit in stroke prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The impact of the Danish National Indicator Project, launched in 2008, has been investigated in a Danish nationwide survey which showed that from 2007 to 2010, the percentage of patients with stroke and ICA stenosis who underwent CEA within 2 weeks increased from 13% to 47% (Witt et al ., ). In the years before this study, our vascular department (Rathenborg et al ., ) and others (Noronen et al ., ) reduced the time from referral to surgery by introducing an accelerated course of examinations – a so‐called fast track.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of the Danish National Indicator Project, launched in 2008, has been investigated in a Danish nationwide survey which showed that from 2007 to 2010, the percentage of patients with stroke and ICA stenosis who underwent CEA within 2 weeks increased from 13% to 47% (Witt et al ., ). In the years before this study, our vascular department (Rathenborg et al ., ) and others (Noronen et al ., ) reduced the time from referral to surgery by introducing an accelerated course of examinations – a so‐called fast track.…”
Section: Discussionmentioning
confidence: 99%
“…National surveys and reports from stroke centres in other countries show that the 14-day time limit is far from being met in all patients (Brown & Naylor, 2009;Vikatmaa et al, 2011;Jetty et al, 2012;Noronen et al, 2012;Purkayastha et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This was mostly as a result of the lack of patient awareness in seeking urgent medical advice, but delay in the diagnostics still occur. 28,31 The two week recommendation is obtained from post-hoc analysis and has not been evaluated in RCTs.…”
Section: Delay and Sexmentioning
confidence: 99%
“…This was mostly as a result of the lack of patient awareness in seeking urgent medical advice, but delay in the diagnostics still occur. 28,31 The two week recommendation is obtained from post-hoc analysis and has not been evaluated in RCTs.…”
Section: Delay and Sexmentioning
confidence: 99%